OPEC and the international oil industry : a changing structure - Al-Chalabi, Fadhil J.; Organization of Arab Petroleum Exporting Countries (Oxford ; New York : Oxford University Press on behalf of the Organization of Arab Petroleum Exporting Countries, 1980)
This book explains how the concession system and the various consortia arrangements among transnational oil companies gave them maximum freedom and flexibility in the control and management of crude oil production and management.
Includes bibliographical references.
lje 22/1/19
Loans
Keywords: Petroleum industry and trade